Pengadaan sarana dan prasarana di Sekolah Dasar Islam Surya Buana Malang - Rokhman, Arif Nur (Maliki Interdisciplinary Journal, 2024)
This article discusses the management of procurement and maintenance of educational facilities at SD Islam Surya Buana Malang. The approach includes in-depth analysis of school needs prior to procurement processes, aimed at optimizing resource utilization and supporting the learning process. Additionally, the school emphasizes sustainable maintenance through planned strategies to ensure all facilities function optimally. Active participation of the school community in maintenance is a key focus, involving all stakeholders to enhance facility management efficiency and quality.